Beyond dreams - Yan, Qianqian (Nanyang Technological University, 2024)
Beyond Dreams is a collection of three intricately woven science fiction narratives that explore the profound intersection between dreams and reality. Each story delves into the psychological and emotional complexities of dreamscapes, where characters confront their desires, fears, and identities. As they navigate these alternate realms, the boundaries between the real and the illusory begin to blur, leading to profound revelations about control, power, and self-awareness. Through imaginative and thought-provoking storytelling, Beyond Dreams examines the human tendency to seek refuge in fantasy while confronting the consequences of losing oneself to the seductive allure of dreams.